Novel-Commentary as a Method of Rethinking the Past and a Form of Authorial Reflection (on the Basis of E. Popov’s „The Real Story of the ’Green Musicians’”) - Mazalevsky, Dmitry (Slavica, 2021)
The article shows how the genre of the novel-commentary by E. Popov «The Real Story of the Green Musicians” allows the author to evaluate his short story, “The Green Musicians”, written 20 years earlier, on the one hand,and to characterize the entire Soviet epoch, on the other. The pretext commented on, serves as a typical text of the Soviet era, written under the influence of that period: the short story is an excellent example of the review of the Soviet times, while the commentary functions as an independent artistic element of the novel. Also, the article offers a classification of a complex and interconnected system of post-textual notes, which are conditionally divided into several levels. Each level of the commentaries serves Popov’s goal of expressing his attitude towards the Soviet nomenclature, which is the underlying theme of his work.